The rpoB mutants destabilizing initiation complexes at stringently controlled promoters behave like “stringent” RNA polymerases in Escherichia coli - Zhou, Yan Ning (National Academy of Sciences, 1998)
In Escherichia coli, stringently controlled genes are highly transcribed during rapid growth, but “turned off” under nutrient limiting conditions, a process called the stringent response. To understand how transcriptional initiation at these promoters is coordinately regulated, we analyzed the interactions between RNA polymerase (RNAP) (both wild type and mutants) and four stringently controlled promoters. Our results show that the interactions between RNAP and stringently controlled promoters are intrinsically unstable and can alternate between relatively stable and metastable states. The mutant RNAPs appear to specifically further weaken interactions with these promoters in vitro and behave like “stringent” RNAPs in the absence of the stringent response in vivo, constituting a novel class of mutant RNAPs. Consistently, these mutant RNAPs also activate the expression of other genes that normally require the response. We propose that the stability of initiation complexes is coupled to the transcription of stringently controlled promoters, and this unique feature coordinates the expression of genes positively and negatively regulated by the stringent response.